A implementação da NBR ISO 14OO1:2004 em organizações: um estudo multicaso - Santos, Nádia Cristina Ribeiro dos (2007)
Organizations have been facing an increasing process of requirements in terms of having a responsible and engaged posture regarding the environment. In this context, organizations have been trying to establish forms of management to be in conformity with the changes of world thinking and behavior. Nowadays, investments in environmental management are some aspects which have been strengthening the positive image of organizations in the market in which the organizations act as well as their image with stakeholders. The concern of the society about the environmental quality and the sustainable use of environment has been reflecting in the elaboration of severe laws. Thus, organizations search for the conformity with the environment and the society through the use of ISO 14001 certification. The certification of environmental management systems has been an efficient tool to reach the expected results in companies, which face seriously the process of continuous improvement. This way, the present work aims to analyze the implementation of the norm ISO 14001:2004 in organizations. The relevance of this study subject can be well supported by the pressure made by all the parts interested on the system of organizations related to the environmental preservation. The research has a qualitative characteristic and the methodology used firstly a theoretical background, which was followed by the interpretation of the norm to provide a greater comprehension and clearance of the context to be dealt with. The organizations were characterized, presented, and afterwards the analysis of the elaborated research was made according to the requirements of the norm. The norm ISO 14001, which is a generic norm that is appropriate to any kind of organization, opens the possibility for different comprehension and interpretation of its requirements. This, a deep study of the environmental aspects of the organizations which search for the conformity with the norm certification should be taken into consideration. Therefore, besides the economic aspects, organizations have been incorporating some actions linked to the quality of environment and the sustainable development into their strategic planning and environmental policies.